History In Evidence: Saxon Britain - Triggs, Tony D (Wayland Publishers Ltd, 1989)
This book uses the clues discovered by archaeologists to reveal what life was for the people who laid the foundations of present day British society.
Keywords: Europe; Great Britain; History